Self-esteem instability and affective instability in everyday life after remission from borderline personality disorder - Santangelo, Philip S.; Kockler, Tobias D.; Zeitler, Marie-Luise; Knies, Rebekka; Kleindienst, Nikolaus; Bohus, Martin; Ebner-Priemer, Ulrich W. (Borderline Personality Disorder and Emotion Dysregulation, 2020)
Borderline personality disorder (BPD) is defined by a pervasive pattern of instability. According to prior findings and clinical theories, self-esteem instability and affective instability are key features of BPD. Previous e-diary studies showed that instability in self-esteem is heightened and that it is highly intertwined with affective instability in BPD in comparison to healthy controls (HC). The present study sought to extend these findings by adding symptomatologically remitted BPD patients (BPD-REM), i.e. former patients with BPD who met four or fewer BPD criteria within the past year, as a comparison group.
Gesehen am 14.11.2023